Inscriptions from the “Pompeii Mausoleum” of Torreparedones (Baena, Córdoba). Notes on Family Relationships - Beltrán Fortes, José (Gerión. Revista de Historia Antigua, 2021)
The set of funerary inscriptions from the “Pompeii mausoleum” (Torreparedones, Baena, Córdoba), engraved on twelve stone urns and discovered in 1833, are indeed the most complete and significant epigraphic record on the incorporation process into Roman citizenship and onomastic Latinization in Hispania. Starting from the analysis of Aureliano Fernández-Guerra’s study, carried out in 1834, a new proposition concerning the family relationship of each person of the gens Pompeia named on them is presented, establishing a new stemma of the familia Pompeia as a hypothesis.